Climate change policy discontinuity & Australia's 2016-2021 renewable investment supercycle. (January 2022) - Simshauser, Paul; Gilmore, Joel
Abstract: The recent history of Australia's National Electricity Market (NEM) from 2012 to 2016 was characterised by coal plant closures, tightening domestic gas market and sharply rising electricity prices. The supply-side response that followed from 2016 to 2021 could only be described as an investment supercycle – 16, 000 MW of plant commitments comprising 26.5 billion across 135 (mostly) Variable Renewable Energy (VRE) projects. We examine causes and the effects of the supercycle. Underlying causes included disorderly plant exit and climate change policy discontinuity in prior periods. Adverse effects in the post-entry environment included connection lags, system strength-related VRE production constraints, ex-post remediation costs, system frequency careering outside normal operating bands, and rising system operator interventions. Market institutions were caught out and subsequently focused on market re-design and resource adequacy reforms. Yet analysis contained in this article reveals the NEM's most pressing problems relate to real-time power system security, not fundamental market design or resource adequacy issues. Resolution requires the establishment of 'missing markets' (i.e. fast frequency, additional operating reserves, ramping, system strength and inertia), and urgently, to restore power system resilience. Key insights for other jurisdictions are climate change policy continuity and policies which serve to defuse the risk of disorderly coal plant exit. Highlights: This article examines Australia's 2016–2021 renewable investment supercycle Analysis reveals 16, 000 MW of projects were committed at 135 locations Not all projects entered seamlessly due to cyclical boom conditions Disorderly coal plant exit and climate policy discontinuity were key factors Australia's market design remains robust but is characterised by missing markets